The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1475-4754.2005.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

CUERDA SECA CERAMICS FROM AL‐ANDALUS, ISLAMIC SPAIN AND PORTUGAL (10TH−12TH CENTURIES AD): INVESTIGATION WITH SEM–EDX AND CATHODOLUMINESCENCE*

Abstract: Since little is known about the cuerda seca technique, our aim has been to complete an initial analysis of 11th‐century cuerda seca by studying fragments from the 10th century (Pechina, Almería) and the 12th century (Mértola and Almería), so as to establish the diachronic evolution of this technique. Characteristics specific to cuerda seca ceramic glazes were investigated using scanning electron microscopy (SEM) and quantitative chemical analysis with energy‐dispersive X‐ray spectrometry (EDX). The chemical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 8 publications
1
24
0
4
Order By: Relevance
“…Comparing our results with several Islamic and HispanoMoresque workshops in the Iberian Peninsula, tin oxide contents of white and blue glazes fall in the range of Islamic tin-glazed ceramics prior to the 13th century (Molera et al, 2001b;Chapoulie et al, 2005;Vendrell-Saz et al, 2006). Previous studies have shown that Islamic workshops used higher SnO 2 contents, which decreased in Hispano-Moresque technology (Molera et al, 1997a;Vendrell-Saz et al, 2006).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Comparing our results with several Islamic and HispanoMoresque workshops in the Iberian Peninsula, tin oxide contents of white and blue glazes fall in the range of Islamic tin-glazed ceramics prior to the 13th century (Molera et al, 2001b;Chapoulie et al, 2005;Vendrell-Saz et al, 2006). Previous studies have shown that Islamic workshops used higher SnO 2 contents, which decreased in Hispano-Moresque technology (Molera et al, 1997a;Vendrell-Saz et al, 2006).…”
Section: Resultssupporting
confidence: 71%
“…The presence of SnO 2 in yellow, green and black glazes was somewhat unexpected, since they are mostly transparent. However, small amounts of tin oxide have been identified in such glazes in 10the12th century Islamic cuerda-seca ceramics from Spain and Portugal (Chapoulie et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the black outline is laid over the white glaze for the green and black technique, for the cuerda seca, the black outline is drawn on the clay body, and then, distinct coloured glazing preparations are applied. Depending on the ceramic surface to be decorated, two techniques are applied: cuerda seca total, when the entire surface is decorated, and cuerda seca parcial, where the decoration is only partial, and the body matrix is visible and forms part of the design [19]. Lustre pottery appeared around the 11th century [20]; however, only few workshops have been found in southern Spain, while 13th century and subsequent century workshops have been well documented [15].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Os dados recolhidos foram, portanto, comparados com a bibliografia existente sobre cerâmica islâmica monocromática e policromática decorada com "verde e manganês" e com "corda seca" parcial e total. Em Portugal, apenas em Palmela (Fernandes 2003) foram realizadas análises arqueométricas à cerâmica "verde e manganês"; por este motivo as características do vidrado de cor preto da cerâmica decorada a "corda seca" total e parcial das cidades de Lisboa e de Mértola foram também consideradas no estudo (Déléry 2006;Chapoulie et al 2005). Em Espanha, a caracterização dessas cerâmicas está mais desenvolvida, permitindo a comparação com diversos sítios arqueológicos encontrados nas cidades de Zaragoza, Valencia, Murcia, Mallorca, Balguer, Denia, Granada, Córdoba, Badajoz (Molera et al 1997(Molera et al , 2001Coll et al 1997;Pérez Arantegui et al 1997;Valdés Fernandez 1985;Pérez Arantegui e Lapuente 2003).…”
Section: Discussionunclassified
“…A utilização de óxido de manganês foi amplamente difundida durante o período islâmico, especialmente para a cerâmica decorada com "verde e manganês" e com "corda seca" parcial e total (Molera et al 1997;Molera 1996;Valdéz Fernández 1985;Coll et al 1997;Déléry 2006;Chapoulie et al 2005;Pérez Arantegui 1997). No entanto, em alguns casos, o óxido de manganês pode ser substituído por óxido de ferro, resultando numa cor castanha/castanha escura, como se comprova na cerâmica islâmica de Palmela e Badajoz (Valdéz Fernández 1985;Ferreira Fernandes 2003).…”
Section: Discussionunclassified